As políticas públicas de valoriz(ação) do trabalho docente na rede de ensino da Serra/ES : a produção de efeitos no “chão da escola” : (De que valor se trata?) - Queiroz, Marcos Gonçalves (2009)
This study aimed at analyzing the teacher valorization policy in elementary schools in the city of Serra-ES, during the city administration taking place between 1997 and 2004. The study uses Yves Schwartz’s ergological perspective and is also based on Marx’s Theory of Value. Therefore, it considers work as a collective activity in which the human being needs to co-construct management and widen its autonomy in order to handle the teaching task in public schools. Education is understood as a non-dimensional value whose mode of operation organization should be turned towards producing education with social quality and commitment to asserting life as a common good value to society. Starting from this premise, the paper realize that the educational policy in the period under study neither strengthened nor provided visibility to other modes of operation of schools, besides valuing the mercantile logic as a policy to organize and attribute value to the activity of education workers. On the other hand, it also realize that even with the statute reform and application of Programa Escola Campeã (Champion School Program) during the administration studied, educators developed strategies of daily struggle and ways of (re)existing to government policies in this period. Thus, school work is not limited to the classroom, but must also be constituted as an act of effective and collective participation in the production of educational policies, which should be co-produced with the ones “in the school ground” so that school education can play its social role of producing the common good. This study can contribute to the need of problematizing the process of attributing value to teaching in its multiple dimensions and also understand administration as production of autonomy and an important aspect in the process of widening and potentializing the ongoing instituting movements of schools in order to improve public education social quality and the value of work management in education organization.